2022
DOI: 10.48550/arxiv.2206.11371
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Set-coloring Ramsey numbers via codes

Abstract: For positive integers n, r, s with r > s, the set-coloring Ramsey number R(n; r, s) is the minimum N such that if every edge of the complete graph KN receives a set of s colors from a palette of r colors, then there is guaranteed to be a monochromatic clique on n vertices, that is, a subset of n vertices where all of the edges between them receive a common color. In particular, the case s = 1 corresponds to the classical multicolor Ramsey number. We prove general upper and lower bounds on R(n; r, s) which impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…The dependence of the exponent of n on b, which comes from iterating Lemma 4.2, is inverse exponential. The authors suggested in problem 6.1 of [9] that stronger bounds than Lemma 4.2 might be true for the set-coloring Ramsey number R(n; r, s), especially in the regime s ≈ r − √ r where we are applying it here. Such improved upper bounds on R(n; r, s) would immediately improve the dependence on b in (5.1).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The dependence of the exponent of n on b, which comes from iterating Lemma 4.2, is inverse exponential. The authors suggested in problem 6.1 of [9] that stronger bounds than Lemma 4.2 might be true for the set-coloring Ramsey number R(n; r, s), especially in the regime s ≈ r − √ r where we are applying it here. Such improved upper bounds on R(n; r, s) would immediately improve the dependence on b in (5.1).…”
Section: Discussionmentioning
confidence: 98%
“…The lower bound is an obvious corollary of the lower bound in Theorem 1.3, while the upper bound involves some extra effort, in particular drawing on recent work of the authors on set-coloring Ramsey numbers [9]. One interesting corollary of this result is that there are positive constants c and c ′ such that 2 clog 2 n ≤ r(K (3) 5 − e, S (3)…”
Section: Theorem 14mentioning
confidence: 91%
See 1 more Smart Citation
“…We prove lower bounds on 𝑟 𝑘 (𝑡; 𝑞, 𝑝), thus giving lower bounds on certain set-colouring Ramsey numbers. However, we are not able to definitively resolve any questions from [4] due to central gaps in our understanding of hypergraph Ramsey numbers. See Section 5 for more on this.…”
mentioning
confidence: 81%
“…A related notion called the set-colouring Ramsey number was introduced by Erdős, Hajnal and Rado in [9] and subsequently studied in [19] and much more recently in [4] and [2]. Borrowing notation from [4], let 𝑅 𝑘 (𝑡; 𝑞, 𝑠) denote the minimum number of vertices such that every (𝑞, 𝑠)-set colouring of 𝐾 (𝑘)…”
Section: Theorem 12mentioning
confidence: 99%